The Impact of Blockchain Technology on the Financial Services Industry And its Reflection on the Digital Economy in the Saudi Market - Ibrahim, Nahla; Alomair, Mohamed (The Arab Journal of Administration, 2023)
The study dealt with the impact of blockchain technology on the financial services industry and its reflection on the digital economy in the Saudi market. Its fiscal year is on 12/31 of each year, whose financial reports and all data about it are available and are listed continuously without interruption in the Saudi financial market during the period from (2018/2021), so the study sample amounted to (63) financial institutions with a total of (400) items. The researcher used the descriptive approach, and used the questionnaire as a basic tool for collecting study data. The study proved the importance and necessity of benefiting from the technology of block chains in invading the Saudi financial services market. Block chains have a significant impact on the financial services industry and the digital economy in the Saudi market. The financial services industry has a significant impact on the digital economy in the Saudi market